Leucine-rich alpha-2 glycoprotein is useful in predicting clinical relapse in patients with Crohn’s disease during biological remission - Naohiro Nakamura; Yusuke Honzawa; Yuka Ito; Yasuki Sano; Naoto Yagi; Sanshiro Kobayashi; Mamiko Aoi; Takashi Tomiyama; Tomomitsu Tahara; Norimasa Fukata; Toshiro Fukui; Makoto Naganuma (Intestinal Research)
Background/Aims Serum leucine-rich alpha-2 glycoprotein (LRG) is a potential biomarker of Crohn’s disease (CD). This study aimed to evaluate the usefulness of LRG in predicting clinical relapse in patients in remission with CD. Methods This retrospective observational study assessed the relationships among patient-reported outcome (PRO2), LRG, and other blood markers. The influence of LRG on clinical relapse was assessed in patients in remission with CD. Results Data of 94 patients tested for LRG between January 2021 and May 2023 were collected. LRG level did not correlate with PRO2 score (ρ = 0.06); however, it strongly correlated with C-reactive protein (CRP) level (r=0.79) and serum albumin level (r=–0.70). Among 69 patients in clinical remission, relapse occurred in 22 patients (31.9%). In the context of predicting relapse, LRG showed the highest area under the curve, followed by CRP level, platelet count, and albumin level. Multivariate analysis revealed that only LRG (P=0.02) was an independent factor for predicting clinical remission. The cumulative non-relapse rate was significantly higher in patients with LRG < 13.8 μg/mL than in patients in remission with LRG ≥ 13.8 μg/mL and normal CRP level (P=0.002) or normal albumin level (P=0.001). Cumulative non-relapse rate was also higher in patients with LRG < 13.8 μg/mL compared to those with LRG ≥ 13.8 μg/mL in patients with L3 or B2+B3 of Montreal calcification. Conclusions LRG is useful in predicting clinical relapse in patients with CD during biological remission. LRG is a useful biomarker for predicting prognosis, even in patients with intestinal stenosis, or previous/present fistulas.